2021
DOI: 10.1177/0022343320982652
|View full text |Cite
|
Sign up to set email alerts
|

Is governmental and societal discrimination against Muslim minorities behind foreign fighters in Syria and Iraq?

Abstract: This study asks whether governmental and societal discrimination against Muslim minorities explains the outflow of foreign fighters from non-Muslim-majority countries to Syria and Iraq. We use data from the ICSR, Soufan Group, Pokalova (2018), and RASM datasets to examine the connection between discrimination directed at Muslim minorities and the number of foreign fighters originating in a country. We apply grievance-based theory to examine whether minority-specific objective discrimination is behind the pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Note that while all the prophets of Islam are male (including those considered in this article), a study has shown that existential therapy also has a positive effect on women's rumination and awareness (Rezapour-Mirsaleh et al, 2022). It has been stated in other research that the political studies made by putting the existential theory in the center offer a solution against discrimination (Heidenreich et al, 2021;Binder, 2022;Mishali-Ram & Fox, 2022). In a different study, it was concluded that Ellison used existential theory to find a solution to the identity problem of African-Americans (Cotkin, 1995;Bassey, 2007;Dokmane, 2017).…”
Section: Discussionmentioning
confidence: 77%
“…Note that while all the prophets of Islam are male (including those considered in this article), a study has shown that existential therapy also has a positive effect on women's rumination and awareness (Rezapour-Mirsaleh et al, 2022). It has been stated in other research that the political studies made by putting the existential theory in the center offer a solution against discrimination (Heidenreich et al, 2021;Binder, 2022;Mishali-Ram & Fox, 2022). In a different study, it was concluded that Ellison used existential theory to find a solution to the identity problem of African-Americans (Cotkin, 1995;Bassey, 2007;Dokmane, 2017).…”
Section: Discussionmentioning
confidence: 77%